A right to discriminate? how the case of Boy Scouts of America v. James Dale warped the law of free association - Koppelman, Andrew; Wolff, Tobias Barrington (New Haven, Conn. ; London : Yale University Press, 2009)
This title demonstrates that the 'right' to discriminate has a long and unpleasant history. Koppelman and Wolff bring together legal history, constitutional theory, and political philosophy to analyze how the law ought to deal with discriminatory private organizations.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Dale, James -- Trials, litigation, etc; Boy Scouts of America -- Trials, litigation, etc; Freedom of association -- United States; Discrimination -- Law and legislation -- United States; Associations, institutions, etc. -- Law and legislation -- United States; Boy Scouts -- Legal status, laws, etc. -- United States; Gays -- Legal status, laws, etc. -- United States; Federal aid to higher education -- United States; Law; LGBTQ+ Interest; Laws of specific jurisdictions & specific areas of law; Discrimination in employment & harassment law